Effects of spin‐lock field direction on the quantitative measurement of spin‐lattice relaxation time constant in the rotating frame (T1ρ) in a clinical MRI system. Issue 12 (10th November 2014) - Yee, Seonghwan; Gao, Jia‐Hong
Abstract : Purpose: To investigate whether the direction of spin‐lock field, either parallel or antiparallel to the rotating magnetization, has any effect on the spin‐lock MRI signal and further on the quantitative measurement of T 1 ρ, in a clinical 3 T MRI system. Methods: The effects of inverted spin‐lock field direction were investigated by acquiring a series of spin‐lock MRI signals for an American College of Radiology MRI phantom, while the spin‐lock field direction was switched between the parallel and antiparallel directions. The acquisition was performed for different spin‐locking methods (i.e., for the single‐ and dual‐field spin‐locking methods) and for different levels of clinically feasible spin‐lock field strength, ranging from 100 to 500 Hz, while the spin‐lock duration was varied in the range from 0 to 100 ms. Results: When the spin‐lock field was inverted into the antiparallel direction, the rate of MRI signal decay was altered and the T 1 ρ value, when compared to the value for the parallel field, was clearly different. Different degrees of such direction‐dependency were observed for different spin‐lock field strengths. In addition, the dependency was much smaller when the parallel and the antiparallel fields are mixed together in the dual‐field method. Conclusions: The spin‐lock field direction could impact the MRI signal and further the T 1 ρ measurement in a clinical MRI system.